2023
DOI: 10.3390/ijms24044062
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptome and Metabolome Analysis of Rice Leaves Response to High Saline–Alkali Stress

Abstract: Rice (Oryza sativa) is one of the most important crops grown worldwide, and saline–alkali stress seriously affects the yield and quality of rice. It is imperative to elucidate the molecular mechanisms underlying rice response to saline–alkali stress. In this study, we conducted an integrated analysis of the transcriptome and metabolome to elucidate the effects of long-term saline–alkali stress on rice. High saline–alkali stress (pH > 9.5) induced significant changes in gene expression and metabolites, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 80 publications
0
24
0
Order By: Relevance
“…Given the deleterious effects of saline-alkaline stress on rice, previous some studies have been conducted to investigate the potential mechanisms by which rice regulates and adapts to saline-alkaline stress conditions. For instance, japonica 'Nipponbare' was used to alleviate the harmful effect of the saline-alkaline stress using magnetized water [50]; japonica 'Tongxi926 was used to dissect the effects of long-term high saline-alkaline stress on rice [36]; indica '93-11 and its polyploidy were used to explore the mechanisms of saline-alkali tolerance [51]; two japonica cultivars 'dongdao-4 and 'jigeng-88 were used to study their differences in tolerance to saline-alkaline stress [16,35,37]; and two indica cultivars 'FL478 and 'IR29 were used to reveal their differences under saline-alkaline stress by regulating Na + transport [13]. These earlier studies have focused mainly on an individual variety, identical subspecies, or their derived populations based on the analysis of physiological, hormonal, transcriptomic, or metabolomic aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the deleterious effects of saline-alkaline stress on rice, previous some studies have been conducted to investigate the potential mechanisms by which rice regulates and adapts to saline-alkaline stress conditions. For instance, japonica 'Nipponbare' was used to alleviate the harmful effect of the saline-alkaline stress using magnetized water [50]; japonica 'Tongxi926 was used to dissect the effects of long-term high saline-alkaline stress on rice [36]; indica '93-11 and its polyploidy were used to explore the mechanisms of saline-alkali tolerance [51]; two japonica cultivars 'dongdao-4 and 'jigeng-88 were used to study their differences in tolerance to saline-alkaline stress [16,35,37]; and two indica cultivars 'FL478 and 'IR29 were used to reveal their differences under saline-alkaline stress by regulating Na + transport [13]. These earlier studies have focused mainly on an individual variety, identical subspecies, or their derived populations based on the analysis of physiological, hormonal, transcriptomic, or metabolomic aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, approximately 20% of the total rice is planted in the saline-alkaline farmlands, and soil saline-alkalization is emerging as one of the major constraints of rice production in China [32]. Previous studies have demonstrated that different genotypes within a species show extensive variations of tolerance to saline-alkaline stress [13,[33][34][35][36][37][38]. These earlier findings have focused mainly on an individual variety, identical subspecies, or their derived populations based on the analysis of physiological, hormonal, transcriptomic, or metabolomic aspects.…”
Section: Introductionmentioning
confidence: 99%
“…BioProject PRJNA896249 (Wang et al, 2023) examined the effects of low N treatment (0.1 mM nitrate for 3 and 18 days) on the root transcriptomes of two barley cultivars. Barley has about 14 RCPs.…”
Section: Hordeum Vulgare (Barley)mentioning
confidence: 99%
“…Low concentrations of ROS can act as secondary messengers and mediate various responses in plant signaling pathways. Accumulation of excessive ROS, however, results in lipid peroxidation and oxidative stress, causing damage to the plasma membrane, destruction of the cell structure, irreversible metabolic dysfunction, and even cell death (Chen et al, 2020; Khanna et al, 2021; Qian et al, 2023). Salt stress can additionally decrease the electron transport rate (ETR) and quantum yield of PSII, thereby reducing photosynthetic performance (Kojonna et al, 2022).…”
Section: Introductionmentioning
confidence: 99%